Piezo voltage controlled planar hall effect devices - Zhang, Bao; Meng, Kang-Kang; Yang, Mei-Yin; Edmonds, K.W.; Zhang, Hao; Cai, Kai-Ming; Sheng, Yu; Zhang, Nan; Ji, Yang; Zhao, Jian-Hua; Zheng, Hou-Zhi; Wang, Kai-You (Nature Publishing Group, 2016)
The electrical control of the magnetization switching in ferromagnets is highly desired for future spintronic applications. Here we report on hybrid piezoelectric (PZT)/ferromagnetic (Co2FeAl) devices in which the planar Hall voltage in the ferromagnetic layer is tuned solely by piezo voltages. The change of planar Hall voltage is associated with magnetization switching through 90° in the plane under piezo voltages. Room temperature magnetic NOT and NOR gates are demonstrated based on the piezo voltage controlled Co2FeAl planar Hall effect devices without the external magnetic field. Our demonstration may lead to the realization of both information storage and processing using ferromagnetic materials.